Are There Soft Skill Ability Different In Gender? - Fita Setiati (Universitas Muhammadiyah Malang, 2023)
The importance of soft skills as a complement to higher education is of concern to all parties, both educational institutions and students. This awareness emerged due to criticism from the business world which stated that there was a gap in the soft skills of job seekers and the world of work. Referring to these conditions, this research attempts to explore how important soft skills are for students and explore differences in the soft skills abilities of male and female students. This research interviewed 40 respondents, namely 20 male students and 20 female students on 8 soft skill variables. The analytical tool used is two way ANOVA to determine the differences in 8 soft skill abilities between male and female students. The research results show that in communication, flexibility, interpersonal, professionalism and work ethics there are differences in abilities between women and men, but overall there is no difference in the soft skills abilities of male and female students.